Keterlibatan Ayah dan Pengambilan Keputusan Karier dalam Konteks Transisi: Bukti dari Mahasiswi Tingkat Pertama yang Merantau di Poltekkes Semarang - Wibisana Dhian Luthfianto; Rizki Setyo Wulandari; Ika Febrian Kristiana; Dian Ratna Sawitri (Poltekkes Kemenkes Semarang, 2026)
This study aimed to examine the relationship between father involvement and career decision-making self-efficacy among first-year female undergraduate students who migrated and did not live with their fathers. This study employed a quantitative correlational design. The participants were 138 first-year female undergraduate students (M age = 18.14 years; SD age = 0.51), recruited through stratified random sampling. Data were collected using the Nurturant Fathering Scale and the Career Decision-Making Self-Efficacy (CDMSE) Scale, and analyzed using Spearman’s Rho. The results indicated a significant positive relationship between father involvement and career decision-making self-efficacy. Additional analysis revealed that age was not significantly related to father involvement but was positively associated with career decision-making self-efficacy. These findings highlight the important role of paternal emotional support in fostering female undergraduate students’ confidence in making career decision, even when separated geographically.